Розробка теоретичних основ для моніторингу та оцінки екологічного стану рекреаційних зон приміських водойм - Єрмаков, Ю. Ю. (Яроче́нко Я. В., 2025)
The ecological state of recreational zones in suburban water bodies is a key factor in preserving biodiversity, maintaining water resource quality, and ensuring safe conditions for public recreation. The increasing anthropogenic impact, particularly water pollution, the intensification of recreational load, and climate change, necessitates the development of effective methods for monitoring and assessing their condition
Keywords: екологія; водні екосистеми; рекреаційні водойми; моніторинг; забруднення